Comparison of The Effectiveness of Interval Training and Circuit Training in Increasing The Endurance in Futsal Extracurricular - Fajar Gumilar; Entan Saptani; Anggi Setia Lengkana (Universitas Negeri Semarang, 2026)
Endurance is an important component in physical fitness which is needed in futsal, because this game requires repetitive activities with varying intensities so that players must be able to maintain optimal performance. However, there are still many futsal extracurricular students who experience rapid fatigue and decreased performance, so effective training methods are needed to increase endurance. This study aims to analyzed the influence and difference in the effectiveness of interval training and circuit training in increasing the endurance of futsal extracurricular students at the junior high school level. The method used is quantitative with a quasi-experimental design through a two-group pretest-posttest approach, which involves two groups. The participants amounted to 22 male students aged 13-15 years from State Junior High School 1 Conggeang who were divided into two groups, each given interval training and circuit training for 12 meetings. The instrument used is a multistage fitness test (bleep test) to measure VO₂max as an indicator of cardiovascular endurance. Data analysis was carried out using the help of SPSS 27 through descriptive tests, normality tests, homogeneity tests, and t tests. The results showed that there was an increase in the average value of endurance in both groups, where the circuit training group increased from 35,845 to 38,645, while the interval training group increased from 36,082 to 39,000. The paired sample t-test showed that both exercise methods had a significant effect on increasing endurance (p < 0.05). However, the results of the independent samples t-test showed no significant difference between the two methods (p = 0.671 > 0.05). Thus, it can be concluded that interval training and circuit training are both effective in increasing endurance, but do not show significant differences in effectiveness. This study provides the implication that both training methods can be used flexibly in fostering students' physical fitness, especially in futsal extracurricular activities.